The Protection of Data Privacy of College Students - Tao Zhiheng (MATEC Web of Conferences, 2022)
Privacy data belongs to big data, and it is personal information from our lives. The common problem is privacy leaking and cyber attacks. The current solution uses a complex algorithm to encrypt data, but it is expensive and inefficient. In the paper, we combine students' information at university to make four layers based on a reliable framework named FMM. The proposed framework FMM, according to different privacy levels, will choose other encryption methods to protect these data and increase efficiency to keep trade-offs.